Intoxicação aguda espontânea e experimental por samambaia (Pteridium aquilinum) em bovinos - Anjos, Bruno Leite dos (2009)
The epidemiology, pathogenesis, clinical and pathological aspects of the spontaneous and experimental poisoning of cattle by bracken fern (Pteridium aquilinum) were studied. Two scientific papers that stemmed from these studies are presented and discussed here. Initially, 6,256 necropsy reports from cattle necropsied during a de 43-year-period (1964-2006) were reviewed. Of those, 15 cases were consistent with acute poisoning caused by the ingestion of P. aquilinum and they occurred in cattle from small farms in the Central region of the State of Rio Grande do Sul, Brazil. In 40% of the farms the disease occurred in small outbreaks affecting several cattle per farm and in 60% only one bovine was affected in each farm. Morbidity and mortality were 17.9% and lethality was virtually 100%. The poisoning was experimentally produced in four calves; it was concluded that exclusively the events of the primary hemostasis due to thrombocytopenia are responsible for the hemorrhages. Blood culture from three affected calves yield the growth of Klebsiella oxytoca, Staphylococcus hyicus and S. aureus, indicating that septicemia, facilitated by neutropenia could have a role in the death of cattle acutely poisoned due to the ingestion of P. aquilinum.